Adaptive Angular-sector Segmentation Radar Target Recognition based on Grey System - Xiao Yongsheng; Huang Lizhen; Zhou Jianjiang (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
The aspect sensitivity of high-resolution range profile (HRRP) leads to the anomalous change of the HRRP statistical characteristic, which is one of inextricable problems on the target recognition based on HRRP. Aiming at the HRRP statistical characteristic, an adaptive angular-sector segmentation method is proposed through based on the grey relational mode. Comparing to the equal interval angular-sector segmentation method, the new method improves the recognition performance. And these simulation results of five kinds of aircraft targets HRRPs prove the feasibility and validity.